Posisi Hassan dalam Reform Islam di Indonesia - Mughni, Syafiq A. (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2017)
The progress of Hassan's attitude and thinking has prompted Muslims to revisit every custom and tradition that has been considered to be well established and taken for granted, as adopted by